2013
DOI: 10.1177/0267659113478322
|View full text |Cite
|
Sign up to set email alerts
|

Mini-extracorporeal circulation minimizes coagulation abnormalities and ameliorates pulmonary outcome in coronary artery bypass grafting surgery

Abstract: Hemostasis is impaired during CABG and coagulation abnormalities often result in clinically relevant organ dysfunctions, eventually increasing morbidity and mortality rates. Fifteen consecutive patients with coronary artery disease submitted to conventional extracorporeal circulation (cECC) have been compared with 15 matched patients, using mini-ECC (MECC). Postoperative lung function was evaluated according to gas exchange, intubation time and lung injury score. In the MECC group, thrombin-antithrombin comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In accordance with other studies, we observed reduced haemodilution until first postoperative day in the MiECC group as measured by significantly lower haematocrit levels and significantly less weight gain [7,25,26]. Our results disprove the theory that haemodilution is a main factor contributing to impaired haemostasis as neither coagulation factors nor bleeding end points were correlated to the degree of haemodilution.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with other studies, we observed reduced haemodilution until first postoperative day in the MiECC group as measured by significantly lower haematocrit levels and significantly less weight gain [7,25,26]. Our results disprove the theory that haemodilution is a main factor contributing to impaired haemostasis as neither coagulation factors nor bleeding end points were correlated to the degree of haemodilution.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the surgical procedure is simplified with a shorter procedural time and would likely be advantageous in minimally invasive procedures, in cases of challenging anatomy, in combined procedures, or in any cases where reduced CPB and aortic cross-clamping time are particularly advisable. [24][25][26][27][28] The crucial time in conventional chordae implantation is the anchoring procedure to the papillary muscle and correct length measurements. These 2 procedures are actually done prior to the ischemic time and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Significant is also the reduction of priming volume, which substantially contributes to the activation of hemostasis (according to inconsistent literature data, purely crystalloid priming leads to hypercoagulation, use of colloids to hypocoagulation). There is a variety of papers in the literature documenting a lower level of systemic inflammatory response syndrome (SIRS) and hemostasis activation when using MiECC to conventional ECC, unfortunately without clear clinical benefit, except for reducing the volume of administered transfusion products [4,5]. Thrombocytes are one of the most affected key components of haemostasis in ECC.…”
Section: Mini Reviewmentioning
confidence: 99%